Pengaruh Model Pembelajaran Role Playing berbantuan E-Magazine DINO terhadap Hasil Belajar Siswa Kelas 4 SDN Telang 1 Bangkalan - Julia Ayu Puspita; Aditya Dyah Puspitasari (Lembaga Yasin AlSys, 2025)
The low learning outcomes of students in the IPAS subject with a social studies component reflected in an average score of 61.6, below the school’s minimum competency standard as well as students’ limited understanding in using polite expressions such as “please” and “thank you,” form the background of this study. The aim is to determine the effect of implementing the Role Playing learning model supported by the digital magazine E-Magazine DINO (Dinamika Interaksi Sosial) on the learning outcomes of Grade IV students at SDN Telang 1 Bangkalan. This study used a quantitative approach with a pre-experimental method and a one-group pre-test post-test design. The sample consisted of 23 students, selected using total sampling. Data analysis results show that |tₕᵢₜᵤₙg| = 10.200 is greater than tₜₐᵦₑₗ = 2.080, and the significance value (2-tailed) is 0.000 < 0.05, indicating that H₀ is rejected and Hₐ is accepted. This means there is a significant difference in learning outcomes before and after the treatment. Therefore, the application of the Role Playing model assisted by E-Magazine DINO has a positive effect on improving student learning outcomes. This study implies the importance of integrating interactive digital media in social learning at the elementary level.